Philosopher in space and time of culture (chronotope of maître à penser). Part 1 - M. M. Rohozha (Ukrainian Cultural Studies, 2017)
The paper deals with the research of philosophic way of life as an invariant of the Western culture. The author tries to revealthe answers to the questions: What is the influence of the time and place of life on a thinking person? Is it possible to put a question in such away? The first part of the paper gives methodological explanation for such putting the questions. Two conceptual strategies of thinking in the contemporary history of philosophy are mentioned – compartmentalismand biographical method. The latter one allows to understand philosophizing through research of maître à penser. Such approach makes possible cultural studies prospect for the life of a philosopher in the context of unique time and space. To designate the uniqueness of time and space, the category of chronotope (M. Bakhtin) is introduced in the paper. Chronotope sets condensed signs in a definite period at the result of which a unique image of a thinker is born in a definite cultural space. The Antiquity image of philosopher is Socrates. Not a biographical person but a mythologized image, Socrates entered the great time of culture and influenced on the Western civilization. Since Socrates, the philosophizing of Antiquity is considered as the spiritual exercises (P.Hadot), in which the spirit of publicity is combined with the inner dialogue with oneself. Late Antiquity changed practical orientation of philosophy by contemplative one. Plotinus is considered as the example of such life style. Medieval culture transmits philosophizing from agora to the monastery, and since the 13thcentury, philosophizing came back to the city space again – to medieval university. Two opposite images of medieval philosophers are considered, Thomas Aquinas and Siger de Brabant, who were didactic examples, full of moral content. Stories about Siger’s life were spread at once after his death as the warning from inheritance; later on he was forgotten. Thomas Aquinas’ life is known as hagiography, didactic story free from details of private life.